The Association Between Consumption of 100% Fruit Juice and Risk of Age-Related Macular Degeneration: Data From the National Health and Nutrition Examination Survey Database - Song, Mi; Chen, Baihua (Frontiers in Nutrition, 2022)
Age-related macular degeneration is the main irreversible blindness disease worldwide. The current study aimed to investigate whether the consumption of 100% fruit juice increases the risk of age-related macular degeneration and find approaches to prevent and reduce the development of age-related macular degeneration from the aspect of dietary habits. A cross-sectional clinical study design was adopted. We screened participants from the 2005-2006 NHANES database. The logistic regression model was used to evaluate the relationship between 100% fruit juice consumption and advanced AMD and to adjust variables such as demographics, general health status, body mass index (BMI), health-related behaviors, systemic complications, and ophthalmic complications. The results show that 100% fruit juice consumption did not affect early AMD and any AMD. High consumers of 100% fruit juice are more likely to develop advanced age-related macular degeneration than those who never drink 100% fruit juice.